Prevalence of chemotherapy-induced peripheral neuropathy in cancer patients in a tertiary care hospital of Mexico - Segovia Sandoval, Karen Patricia; Guillen-Nuñez, Maria del Rocio; Juarez-Lemus, Angel Manuel; Ahuactzin Avendaño, Tania Helaine; Sanchez Ortega, Ana Lady; Viveros Aguilar, Frida Paola (Journal of Drug Delivery and Therapeutics, 2025)
Objective: To determine the prevalence of chemotherapy-induced peripheral neuropathy in cancer patients in a tertiary care hospital of Mexico.  Design: A retrospective, cross-sectional, observational and descriptive study conducted from January 2018, to December 2022, by review of patients' medical records.Main outcome measures: Identify the most associated oncologic diagnosis, chemotherapeutic agents, main clinical manifestations, pain intensity and the most frequently used therapeutic drugs. Descriptive data analysis was performed.Results: A total of 250 patients were enrolled in this retrospective study, representing 29.65% of those treated at the Pain Clinic.. The mean age was 59 ± 11.3 years, and 84.4% were female. The most frequent diagnosis was breast cancer (n=126, 50.4%). Paresthesia was identified as the main symptom (53.2%). Paclitaxel was the chemotherapeutic agent most commonly used (55.2%), and pregabalin was the most prescribed treatment (39.6%). Fatigue was the most frequent comorbid symptom (26.4%, n=66).Conclusion: The prevalence found was similar than reported in different studies. The distribution of sex, age, commonly used chemotherapeutic agents, and neuromodulatory treatment was similar to reports from other countries. The findings highlight the need for patient education and medical staff training to identify early signs of neuropathy and ensure timely referrals. Keywords: Cancer pain, chronic pain, chemotherapy-induced peripheral neuropathy